Performance of narrow band internet of things (NBIoT) networks - Bhebhe, Mbongeni (Department of Electrical Engineering, 2020)
Narrow Band Internet of Things (NBIoT) is a Low Power Wide Area Network (LPWAN) technology that has been standardised by 3GPP in Release 13 to work in cellular networks [15]. The main characteristics of NBIoT are its extended coverage compared to other cellular technologies such as LTE; its high capacity is due to its narrow channel bandwidth of 180 KHz, which also supports the possibility of these devices having a long battery life of up to 10 years, as well as low device complexity - all of which result in low device costs [2]. NBIoT can be deployed in one of three different options, namely: a) standalone, b) in-band and c) guard band deployment mode. These characteristics of NBIoT makes it very useful in the IoT industry, allowing the technology to be used in a wide range of applications, such as health, smart cities, farming, wireless sensor networks and many more [1] [25]. NBIoT can be used to realise the maximum possible spectral efficiency, thereby increasing the capacity of the network. Penetration of NBIoT in the market has dominated other LPWANs like Sigfox and LoRA, with NBIoT having a technology share of close to 50 percent [31]. This study is aimed at exploring the deployment options of NBIoT and determining how network operators can realise the greatest value for their investment by efficiently utilising their allocated spectrum. The main target is to derive the best parameter combination for deployment of the NBIoT network with acceptable error rates in both the uplink and the downlink. Different characteristics of NBIoT were discussed in this study, and the performance of the various approaches investigated to determine their efficiency in relation to the needs of the IoT industry. The error rates of NBIoT, when used in an existing LTE network, were the main focus of this study. Software simulations were used to compare the different parameter settings to see which options provide the best efficiency and cost trade-offs for structuring an NBIoT network. The results of the tests done in this study showed that the error rates are lower for standalone deployment mode than for in-band mode, which is mainly due to less interference in standalone mode than in in-band mode. The results also show that data transmitted in smaller Transport Block Size (TBS) in the Down Link (DL) has less errors than if it’s transmitted in larger blocks. The results also show that the error rate gets lower as the number of subframe repetition increases in the downlink, which is mainly due to the redundancy in sending the same data multiple times. However in the uplink, the results show that the error rates are comparable when the signal has poor quality.